AutoCAD 2015 and AutoCAD LT 2015 Bible - Finkelstein, Ellen; Ambrosius, Lee (Wiley, 2014)
The perfect reference for all AutoCAD users AutoCAD 2015 and AutoCAD LT 2015 Bible is the book you want to have close at hand to answer those day-to-day questions about this industry-leading software. Author and Autodesk University instructor Ellen Finkelstein guides readers through AutoCAD 2015 and AutoCAD LT 2015 with clear, easy-to-understand instruction and hands-on tutorials that allow even total beginners to create a design on their very first day. Although simple and fundamental enough to be used by those new to CAD, the book is so comprehensive that even Autodesk power u.